Work Conflict and Work Stress: Effects on Employee Performance at PT Telkom STO Parepare - Ruslan Abdullah; Irawati Nur; Megawati Beddu; Arfandy Dinsar; Anita (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to determine whether work conflict and stress partially and simultaneously influence the performance of employees at PT Telkom STO Parepare. The sampling method used in this research is saturated sampling with a total of 35 samples. The analysis method used in this study is multiple linear regression analysis. The results of this study indicate that, partially, the Work Conflict variable (X1) shows a t-value > t-table value, namely 2.960 > 2.034, with a significance value of 0.006 < 0.05. This proves that the work conflict variable has a significant influence on employee performance. Meanwhile, the Work Stress variable (X2) also shows a t-value > t-table value, namely 2.281 > 2.034, with a significance value of 0.029 < 0.05. This indicates that the work stress variable has a significant influence on employee performance. Furthermore, the F-test shows that Work Conflict and Work Stress have a significant simultaneous influence on employee performance (Y), with an F-value of 50.606 > F-table value of 4.14, and a significance level of 0.000 < 0.05. Based on the results of this study, it can be concluded that there is a significant partial and simultaneous influence between work conflict and work stress on employee performance at PT Telkom STO Parepare.